2013
DOI: 10.7717/peerj.148
|View full text |Cite
|
Sign up to set email alerts
|

On the reproducibility of science: unique identification of research resources in the biomedical literature

Abstract: Scientific reproducibility has been at the forefront of many news stories and there exist numerous initiatives to help address this problem. We posit that a contributor is simply a lack of specificity that is required to enable adequate research reproducibility. In particular, the inability to uniquely identify research resources, such as antibodies and model organisms, makes it difficult or impossible to reproduce experiments even where the science is otherwise sound. In order to better understand the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(211 citation statements)
references
References 34 publications
11
194
1
2
Order By: Relevance
“…What is more, only 44% of publications provide enough information -for instance, on the supplierfor researchers to be able to purchase the same antibody 7 . The quality of the documentation that accompanies batches (such as on functionality in different assays) is enormously variable 2 ; even when it is provided, it may not correspond to the batch supplied 8 .…”
Section: Wildly Variablementioning
confidence: 99%
“…What is more, only 44% of publications provide enough information -for instance, on the supplierfor researchers to be able to purchase the same antibody 7 . The quality of the documentation that accompanies batches (such as on functionality in different assays) is enormously variable 2 ; even when it is provided, it may not correspond to the batch supplied 8 .…”
Section: Wildly Variablementioning
confidence: 99%
“…However, as has long been bemoaned by database curators and documented recently by Vasilevsky and colleagues, these resources are not very well identified in the scientific literature 11 . Vasilevsky and colleagues found that researchers did not include sufficient detail for most key research resources to allow someone to identify conclusively an antibody, a genetically modified animal, or cell lines, for example.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 51%-89% of published research cannot be reproduced in other laboratories. [18][19][20][21][22] This problem has been highlighted by a number of recent, high-profile commentaries from the pharmaceutical industry, 18,19,23 funding agencies, including the National Institutes of Health, 24,25 scientific journals, 26,27 veterinarians, 28 academics, and biostatisticians. [29][30][31][32][33][34][35][36] This is of particular importance when animal models are used to advance the development of clinical therapeutics.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%